An improved modulation technique suitable for a three level flying capacitor multilevel inverter - Mahafzah, Khaled A.; Negry, Raneem M.; Obeidat, Mohammad A.; Alsalem, Hesham (International Journal of Electrical and Computer Engineering (IJECE), 2024)
This research paper introduces an innovative modulation technique for controlling a 3-level flying capacitor multilevel inverter (FCMLI), aiming to streamline the modulation process in contrast to conventional methods. The proposed simplified modulation technique paves the way for more straightforward and efficient control of multilevel inverters, enabling their widespread adoption and integration into modern power electronic systems. Through the amalgamation of sinusoidal pulse width modulation (SPWM) with a high-frequency square wave pulse, this controlling technique attains energy equilibrium across the coupling capacitor. The modulation scheme incorporates a simplified switching pattern and a decreased count of voltage references, thereby simplifying the control algorithm.